Evaluation of The Role of Development Strategy in Growth of Operating Profit On the Example of SemiFinished Food Production Enterprise - Tristan Jincharadze (European Scientific Journal, ESJ, 2020)
It is very important to evaluate how well the implementation process of the strategy a company has chosen is going. To make such evaluations it is important to Analyse customer relations, Study how well internal business processes are organized, Evaluate growth and development perspectives and Analyse and summarise financial results. In this article we will pay attention on financial results, in particular the analysis of changes in operating income. Three factors which cause changes to profit while implementing the strategy are: volume, prices and productivity. In Our opinion, using the method mentioned in this article, it becomes possible to calculate the contribution that strategy makes to the growth of profit.